2003
DOI: 10.1128/jcm.41.4.1769-1771.2003
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Dissemination of Yersinia enterocolitica Strains with Various Susceptibilities to Nalidixic Acid

Abstract: Ten epidemiologically related Yersinia enterocolitica clinical isolates were studied. Six isolates were nalidixic acid resistant (MIC > 512 g/ml), with mutations in the quinolone resistance-determining region (QRDR) of the gyrA gene, suggesting clonal dissemination of a nalidixic acid-susceptible Y. enterocolitica strain which has acquired different mutations generating resistance to nalidixic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…These results agree with those described by Sánchez-Céspedes et al (21). These authors showed the clonal spread of one strain that became resistant to nalidixic acid by acquiring mutations in the gyrA gene.…”
supporting
confidence: 83%
“…These results agree with those described by Sánchez-Céspedes et al (21). These authors showed the clonal spread of one strain that became resistant to nalidixic acid by acquiring mutations in the gyrA gene.…”
supporting
confidence: 83%
“…It is interesting, in this respect, that E. faecium isolates that harbored amino acid substitutions in the DNA mismatch repair proteins MutS and MutL belong to CC17 (61), which may suggest that CC17 isolates are more prone to undergo mutations in, e.g., parC or gyrA, conferring high-level resistance to quinolones. Clonal dissemination of quinolone resistance was also reported among methicillin-resistant Staphylococcus aureus, Neisseria gonorrhoeae, Salmonella enterica serotype Typhimurium strain DT 104, Streptococcus pneumoniae, and Yersinia enterocolitica (28,46,48).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other Enterobacteriaceae, small numbers of Y. enterocolitica resistant to nalidixic acid have been reported to date (Sánchez-Céspedes et al, 2003;Capilla et al, 2004;Fà brega et al, 2010;Sihvonen et al, 2011;Fredriksson-Ahomaa et al, 2012). Although target gene mutations in gyrA are the primary mechanism of resistance to nalidixic acid, efflux pump activity, also contributes to support this phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Within these loci, the quinoloneresistance-determining region (QRDR) is a mutational hot spot (Fà brega et al, 2010). Several mutations have already been identified in gyrA in Yersinia enterocolitica, the most common of which lead to amino acid substitutions at Ser-83 and Asp-87, conferring resistance to nalidixic acid (Sánchez-Céspedes et al, 2003;Capilla et al, 2004;Sihvonen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%